The Radical "Second Life" of Vilhjalmur Stefansson - Srebrnik, Henry F. (ARCTIC, 1998)
. The American Communist movement included numerous "front" organizations which championed the political views and advanced the goals of the Soviet Union. Among them were movements whose main aim was to provide support for the Soviet project to establish a Jewish socialist republic in the Birobidzhan region in the far east of the USSR. One of the organizations prominent in this campaign was the American Committee for the Settlement of Jews in Birobidjan. The Committee, also called Ambijan, was formed in 1934. It sought to attract to its ranks philanthropists and men of financial prominence or wealth. As well, it captured public attention through the recruitment of celebrities and fairly eminent public figures who, while not known Communists, were sympathetic to the politics of the USSR. Though their detractors called them "fellow-travellers," these people often proved to be valuable assets to the cause. One champion of the Birobidzhan scheme, and a vice president of Ambijan after 1936, was the prominent Arctic explorer, scientist, and author Vilhjalmur Stefansson. A tireless proponent of settlement in Birobidzhan, he appeared at countless meetings, dinners, and rallies, recounting the exploits, real and imagined, of Jewish settlers trying to build a socialist republic in the tundra of the Soviet Far East. Given his fame and stature, he proved an invaluable resource for the leadership of Ambijan. .